Increasing Status of Criminal Gangs in Post-conflict Nepal: The Case of Kathmandu Valley - K.C., Dipesh Kumar (Kathmandu School of Law Review, 2018)
The paper has objectives: to explain the gang phenomenon in Kathmandu Valley, their causes of effectiveness, the politicization of criminal gangs in the post-conflict situation, and the counter-product of governmental intervention. It has discussed the present challenges that the Valley has been facing, and possibilities of future challenges it has to confront. Youths’ identity crisis, social opportunities, rapid urbanization and incorrect approaches to gangs’ suppression are the key frameworks to find out the causes behind the criminal gangs being increasingly active in Kathmandu Valley. Interestingly, marginalized and suppressed social members feel secure and protected in the gang. The researcher has identified that the criminal gangs are the social fact of the rapidly urbanized society of the Kathmandu Valley where prevention policies have been neglected a lot. As a result, suppression policies have failed, thus, the new forms of gang-related crimes have emerged and expanded far and huge. DOI: https://doi.org/10.46985/jms.v6i2.205